HIDROLISIS BATANG PADI DENGAN MENGGUNAKAN ASAM SULFAT ENCER - N. Soeseno, N. Chiptadi dan S. Natalia, Akbarningrum Fatmawati, (Jurnal Teknik Kimia, 2008)
Glucose is usually known as a source of energy for organisms. Fermentation of glucose canproduce many useful products such as ethanol, which can be used for renewable energy source,replacing fuel oil. Glucose can be derived from many foodstuffs such as cassava, yam, grass,wheat, potato, corn, etc. Such foodstuffs contain polysaccharide that can be hydrolyzed intoglucose. Rice straw is one of natural waste materials with high cellulose content which can beutilized for glucose production to avoid competition with foodstuff needs. In this research diluteacid hydrolysis of rice straw is investigated using slurry concentration of 30% w/v. The effects of temperature (70, 85, 100oC), sulfuric acid concentration (0.3; 0.6; 0.9 %v/v), and particle size ofrice straw (8, 10, 20 mesh) on the reducing sugar yield are observed. In this research, the resultshows that the increase of set temperature will increase the final reducing sugar concentration.The decreasing size of the rice straw will increase the reducing sugar concentration. The higherthe sulfuric acid concentration the higher reducing sugar concentration will be. The maximumcondition obtained from this research is at the set temperature of 100oC, sulfuric acidconcentration of 0.9 %v/v, and size of rice straw of 20 mesh (0.841 mm). This condition willproduce 1.1583 gram/liter of final reducing sugar concentration with 38.61 mg/g of yield.